2015
DOI: 10.1088/1367-2630/17/4/045020
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic model for shape resonance control of diatomics by intense non-resonant light

Abstract: We derive a universal model for atom pairs interacting with non-resonant light via the polarizability anisotropy, based on the long range properties of the scattering. The corresponding dynamics can be obtained using a nodal line technique to solve the asymptotic Schrödinger equation. It consists of imposing physical boundary conditions at long range and vanishing the wavefunction at a position separating the inner zone and the asymptotic region. We show that nodal lines which depend on the intensity of the no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(63 citation statements)
references
References 47 publications
3
60
0
Order By: Relevance
“…It is worthwile mentioning that the dependence of the parallel and perpendicular components of the static (ω = 0) dipole polarizability at large interatomic distances has been discussed in several papers [135][136][137] …”
Section: Polarizability Of Feshbach Moleculesmentioning
confidence: 99%
“…It is worthwile mentioning that the dependence of the parallel and perpendicular components of the static (ω = 0) dipole polarizability at large interatomic distances has been discussed in several papers [135][136][137] …”
Section: Polarizability Of Feshbach Moleculesmentioning
confidence: 99%
“…It consists in accounting for all short-range physics by the choice of the node positions of the scattering wavefunction at intermediate interparticle distances. This formalism has been extended to shape resonances [13] and to the control of shape resonances by non-resonant light which couples the different partial ℓ-waves via the polarizability anisotropy [14]. In particular, we have previously shown that an intensity-dependent nodal line is sufficient to account for the effect of the coupling to the non-resonant light at short-range.…”
Section: Introductionmentioning
confidence: 99%
“…While a multi-channel treatment is essential to describe the strong hybridization of the rovibrational motion due to the coupling with the non-resonant light [15,16], the position and width of the resonance are found to vary linearly with field intensity up to fairly large intensities [14]. When treating the interaction with the nonresonant light as a perturbation and truncating the perturbation expansion at the first order, resonance position and width are determined by the field-free wavefunctions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations